2016
DOI: 10.1155/2016/2824595
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Limitations of the Center for Epidemiologic Studies-Depression Scale for Assessing Depressive Symptoms among Adults with HIV/AIDS: A Rasch Analysis

Abstract: The Center for Epidemiological Studies-Depression (CES-D) scale is a widely used measure of depressive symptoms, but its psychometric properties have not been adequately evaluated among adults with HIV/AIDS. This study used an item response theory approach (Rasch analysis) to evaluate the CES-D's validity and reliability in relation to key demographic and clinical variables in adults with HIV/AIDS. A convenience sample of 347 adults with HIV/AIDS (231 males, 93 females, and 23 transgenders; age range 22–77 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 55 publications
6
34
1
Order By: Relevance
“…Previous research suggests that the CES-D may be biased when assessing individuals of racial and ethnic minorities. For example, African–Americans may be more likely to adhere to the negative interpersonal items on the CES-D 22. However, we found that although a slightly higher proportion of non-whites had CES-D scores ≥10 relative to whites (18.1% vs 21%, respectively), this finding was not statistically significant.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous research suggests that the CES-D may be biased when assessing individuals of racial and ethnic minorities. For example, African–Americans may be more likely to adhere to the negative interpersonal items on the CES-D 22. However, we found that although a slightly higher proportion of non-whites had CES-D scores ≥10 relative to whites (18.1% vs 21%, respectively), this finding was not statistically significant.…”
Section: Discussioncontrasting
confidence: 77%
“…Thus, our study is not the first to report psychometric limitations of the CES-D scale when applied to multiple racial groups. Previous studies warned that CES-D scale scores should be interpreted with caution in different populations, particularly when comparing scores across racial groups (59, 60). …”
Section: Discussionmentioning
confidence: 99%
“…We note recent analyses of depression in HIV-infected populations that question the validity of the CESD when used with heterogeneous samples of diverse genders (including transgender) and racial groups ( n = 347) (Gay et al ., 2016 ). Given the larger sample size and greater homogeneity in this East African, care-engaged study population, we believe the results to be a valid indication of the associations among depression, HIV viral load and cognition.…”
Section: Limitationsmentioning
confidence: 99%